Upgrading combined anaerobic-aerobic UASB-FPU to UASB-DHS system: Cost comparison and performance perspective for developing countries. (15th February 2021) - Mazhar, Mohd Aamir; Khan, Nadeem A.; Khan, Afzal Husain; Ahmed, Sirajuddin; Siddiqui, Asif Ali; Husain, Azhar; Rahisuddin,; Tirth, Vineet; Islam, Saiful; Shukla, Neeraj Kumar; Changani, Fazlollah; Yousefi, Mahmood; et al.
Abstract: This study determined the performance of upgraded sewage treatment plant (STP) based on an anaerobic-aerobic system consisting Up-flow Anaerobic Sludge Blanket (UASB) reactor, Final Polishing Unit (FPU) and Down-flow Hanging Sponge (DHS) system, treating municipal wastewater located at Dhandhupura, Agra, Uttar Pradesh (India). The performance evaluation of STP were based on the removal efficiency of parameters like Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS) and Volatile Suspended Solids (VSS). The results exhibits improved BOD, COD, TSS and VSS removal efficiency for UASB-DHS system (92.01%, 82.26%, 91.02%, 92.88%) as compared to UASB-FPU (81.67%, 74.35%, 83.72%, 83.41%) respectively. In addition, this study compares the UASB-DHS system with other post-treatment methods based on their treatment cost and removal efficiency. The technology ranking analysis showed that the UASB-DHS system scored the highest desirability value of 6.77 followed by MBR and ASP technology having a score of 5.17 and 5.11 respectively. The results demonstrated that the UASB-DHS system outperformed the existing UASB-FPU system and met the Indian standards for effluent discharge i.e. BOD less than 30 mg/l. Therefore, the treated sewage can be considered for cultivation, irrigation purpose and safely discharged into water bodies. Moreover, the cost analysis indicates that the UASB-DHS system requires less energy in operation, low expenses in sludge handling and comparatively small area required for post-treatment operation. Hence, this work proposed an economical and efficient approach for the treatment of municipal wastewater particularly for developing countries. Graphical abstract: Image 1 Highlights: UASB-DHS integrated technology is sustainable approach for treatment developing countries. UASB-DHS system has the highest removal efficiency with least laborious maintenance. This study compares the UASB-DHS system with other post-treatment methods on cost and removal efficiency. UASB-DHS integrated technology system exhibits an economical and efficient approach. UASB-DHS system exhibits improved removal efficiency (max 93%) in reducing BOD, COD, TSS, VSS.